2007
DOI: 10.1029/2006jf000474
|View full text |Cite
|
Sign up to set email alerts
|

Development and response of a coupled catchment fan system under changing tectonic and climatic forcing

Abstract: [1] Sediment fans are a potentially useful and underexploited recorder of Earth's climatic and tectonic history, but historical observations have led to conflicting views on the importance of tectonic, climatic, and lithologic variables in controlling fan morphology and deposition. A one-dimensional model of a sediment fan and its associated catchment is used to explore the sensitivity of such simple sediment routing systems to perturbations in fault slip and precipitation rates. A transport-limited catchment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 56 publications
7
125
0
Order By: Relevance
“…Erosional base-level falls tend to result in temporary thin fans, and tectonic base-level falls tend to result in prolonged accumulation of thick fans (Bull, 1977). There are strong relationships between active orogenic environments and thick accumulations of young fan deposits (Beaty, 1970;Densmore et al, 2007). On the other hand, continued lack of tectonic uplift will change the depositional environment to an erosional environment where pedimentation or flooding events are the main process operating on the landscape (Bull, 1977;Haug et al, 2010).…”
Section: Geographical Setting Of El'gygytgyn Cratermentioning
confidence: 99%
“…Erosional base-level falls tend to result in temporary thin fans, and tectonic base-level falls tend to result in prolonged accumulation of thick fans (Bull, 1977). There are strong relationships between active orogenic environments and thick accumulations of young fan deposits (Beaty, 1970;Densmore et al, 2007). On the other hand, continued lack of tectonic uplift will change the depositional environment to an erosional environment where pedimentation or flooding events are the main process operating on the landscape (Bull, 1977;Haug et al, 2010).…”
Section: Geographical Setting Of El'gygytgyn Cratermentioning
confidence: 99%
“…2b). These values are chosen because they generate response times within the range of observations from normal fault-bounded sedimentary systems that have responded to changes in slip rate (Densmore et al, 2007;Armitage et al, 2011).…”
Section: Erosion By Sediment Transportmentioning
confidence: 99%
“…In other cases, however, a change in climatic forcing may exert the strongest control on fan slope and morphology. Densmore (2007) found that sediment transport efficiency controls the long profile slope of fans rather than the dominance of debris flow or fluvial activity. One uniting observation is that fans have distinct spatial variation.…”
Section: Alluvial Fansmentioning
confidence: 99%
“…The processes that control fan morphology are complex and include interactions between uplift, subsidence, climate, depositional processes, and lithology (Blair and McPherson, 1994; 6 Densmore et al, 2007). Alluvial fans commonly form in regions of active uplift where normalfaulted footwall blocks form catchments and material is deposited onto subsiding down-thrown hanging wall blocks.…”
Section: Alluvial Fansmentioning
confidence: 99%